The concept of “francophony” and its influence on the development of French sociolinguistics and linguodidactics - Kamilla Kurbanova-Ilyutko (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The article examines how the concept of «francophonia», which has become established and spread in culture and science as a result of the works of L.S. Senghor, influenced the vectors of development of the French sociolinguistics and linguodidactics. If earlier the attention of scientists was focused on the French language of France, its normalization and codification, and any deviation from the norm caused censure (in this context, we mean regional uses that did not correspond to the norm), then with the advent of the concept of «francophonia», territorial varieties of the French language became separate object of study, thereby giving rise to a new direction of language variation studies, aimed at exploring the richness and originality of regional varieties of the French language. The article gives the names of the first collective monographs dedicated to the peculiarities of the French language, depending on its territorial affiliation and social stratification. As for the French linguodidactics, until the last quarter of the 20th century, its development took place in two directions: teaching French as a mother tongue and teaching French as a foreign language. Here the concept of «francophonia» played an important role, revealing another independent category of French speakers who speak it as a second language. Being initially the achievement of theoretical linguodidactics, the concept of «French as a second language» provoked the development and creation of new teaching aids, mainly for French-speaking countries (with French as a second language for the majority of the population), and later for allophones arriving in France and other French-speaking countries (with French as a mother tongue for the majority of the population).